2007
DOI: 10.1302/0301-620x.89b1.18222
|View full text |Cite
|
Sign up to set email alerts
|

A systemic provascular response in bone marrow to musculoskeletal trauma in mice

Abstract: Post-natal vasculogenesis, the process by which vascular committed bone marrow stem cells or endothelial precursor cells migrate, differentiate and incorporate into the nacent endothelium and thereby contribute to physiological and pathological neurovascularisation, has stimulated much interest. Its contribution to neovascularisation of tumours, wound healing and revascularisation associated with ischaemia of skeletal and cardiac muscles is well established. We evaluated the responses of endothelial precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Significant increases in the number of circulating EPCs have been detected in humans and animals after traumatic brain injuries [31], skin burns [32], [33], sepsis [34], [35], heart failure [36]and acute lung injury [37], [38]. Furthermore, some authors reported the mobilization of CD34+cells from bone marrow after an isolated bone fracture in rodents [10], [11] and humans [14]. As a result, the stromal cell-derived factor-1/CXC chemokine receptor 4 (SDF-1/CXCR-4) axis has been recognized as a pivotal mechanism for the recruitment of EPCs to ischemic and damaged tissues [39], [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant increases in the number of circulating EPCs have been detected in humans and animals after traumatic brain injuries [31], skin burns [32], [33], sepsis [34], [35], heart failure [36]and acute lung injury [37], [38]. Furthermore, some authors reported the mobilization of CD34+cells from bone marrow after an isolated bone fracture in rodents [10], [11] and humans [14]. As a result, the stromal cell-derived factor-1/CXC chemokine receptor 4 (SDF-1/CXCR-4) axis has been recognized as a pivotal mechanism for the recruitment of EPCs to ischemic and damaged tissues [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…showed that CD34+cells are recruited to fracture sites and contribute to fracture healing when they are intravenously injected into nude rats with non-healing femoral fractures [6]. Although the mechanism of EPC mobilization from bone marrow is not fully understood, there is accumulating evidence that musculoskeletal trauma may cause a systemic, pro-vascular response in rodent bone marrow [10][12] and in human [13]–[15] bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that fracture may induce the mobilization of EPCs from the BM to fracture site, by way of transport through the PB as a way to augment neovascularization and ultimately bone healing. As supportive data, systemic delivery of EPCs developed a favorable environment for fracture healing by enhancing angiogenesis and osteogensis …”
Section: Discussionmentioning
confidence: 95%
“…This new paradigm uses pharmacologic induction of mobilization and endogenous mechanisms of cell homing and engraftment to sites of injury. It is plausible this strategy simply mimics and amplifies normal repair mechanisms as progenitor cells are mobilized to the PB after stroke [41], vascular trauma [20], musculoskeletal trauma [31,32], fracture [3,34], distraction osteogenesis [34], and myocardial infarction [60]. An important pathway for stem cell mobilization is the SDF-1/CXCR4 axis and there are recent data supporting the concept that transient disruption of this receptor-ligand complex through the CXCR4 antagonist, AMD3100, enhances bone formation in vivo [57,59].…”
Section: Discussionmentioning
confidence: 99%
“…Alm et al [3] found circulating plastic-adherent MSCs are more common in patients after fracture than in subjects who had not fractured. Lee et al [35] reported an increase in circulating EPCs after tibial fracture in female BALB/c mice, peaking at Day 3 postfracture, while Laing et al [31] report a slightly early time course in response to tibial fracture in C57BL/6 mice. We found the largest increase in EPCs at Day 7, which may indicate the true peak of EPC mobilization in our model was at an earlier time point.…”
Section: Discussionmentioning
confidence: 99%